2016
DOI: 10.1016/j.nut.2016.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake and childhood leukemia: The Diet and Acute Lymphoblastic Leukemia Treatment (DALLT) cohort study

Abstract: Objective Children with acute lymphoblastic leukemia (ALL) are at elevated risk for nutrition-related morbidity both during and after therapy. We present the demographic characteristics and nutrient intake at study entry of a prospective cohort in which evaluating dietary intake in children diagnosed with ALL was investigated. Methods Dietary intake data were collected for participants enrolled on the Dana-Farber Cancer Institute ALL Consortium Protocol. Dietary intake was assessed with a food frequency ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 36 publications
5
35
0
1
Order By: Relevance
“…Finally, despite our restricted analysis for dietary components, our study concurs with previous studies demonstrating very few patients meet dietary recommendations. A mere 10% of participants met dietary guidelines for fruits and vegetables; a figure lower than previously reported data and aligned with others . In the light of the increased risk of nutrition‐related morbidities, our results reflect an opportunity for intervention to further health outcomes among this at‐risk population …”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Finally, despite our restricted analysis for dietary components, our study concurs with previous studies demonstrating very few patients meet dietary recommendations. A mere 10% of participants met dietary guidelines for fruits and vegetables; a figure lower than previously reported data and aligned with others . In the light of the increased risk of nutrition‐related morbidities, our results reflect an opportunity for intervention to further health outcomes among this at‐risk population …”
Section: Discussionsupporting
confidence: 62%
“…Recent evidence has demonstrated the feasibility of exercise‐based interventions during the intensive phase of treatment . Additional data are needed on the feasibility of lifestyle change during different treatment phases . Treatment of cancer may be an optimal time for dietary and exercise interventions especially if interventions are incorporated into existing treatment protocols and approached as other routine supportive care interventions …”
Section: Discussionmentioning
confidence: 99%
“…Considering the observation of both reduced toxicities and inferior survival in the Hispanic cohort, the possibility of suboptimal drug exposure in these patients likely deserves further inquiry. Thus, while differences in both host and leukemia biology are prognostically important, future studies will also focus on host pharmacogenomics, detailed analyses of nutrition status and obesity trends, interpatient differences in biomarkers of drug exposure, frequency of drug interruptions for toxicity, and oral chemotherapy adherence.…”
Section: Resultsmentioning
confidence: 99%
“…The main sources of vitamin D are production in the skin through sunlight exposure, diet, and vitamin D supplements [7,11]. Vitamin D (D 2 Children with ALL may be at increased risk of vitamin D deficiency due to impaired sun exposure and impaired vitamin intake [12]. A retrospective study in 86 pediatric cancer patients with a median age of 7 years revealed vitamin D deficiency in 63% at diagnosis [13].…”
Section: Introductionmentioning
confidence: 99%